Do Skilled Nursing Facilities Selected to Participate in Preferred Provider Networks Have Higher Quality and Lower Costs?. (15th August 2018) - Huckfeldt, Peter J.; Weissblum, Lianna; Escarce, José J.; Karaca‐Mandic, Pinar; Sood, Neeraj
Abstract : Objective: To determine whether skilled nursing facilities (SNFs) chosen by health systems to participate in preferred provider networks exhibited differences in quality, costs, and patient outcomes relative to other SNFs after accounting for differences in case mix. Data Sources: Medicare provider and claims data, 2012 and 2013. Study Design: We compared SNFs included in preferred networks relative to other SNFs in the same market, prior to the establishment of preferred provider networks. Data Extraction Methods: We linked the SNFs in our sample to facility characteristics and quality data. We identified SNF admissions and hospitalizations in claims data and limited the analysis to patients discharged from the hospitals in our sample. We obtained patient characteristics from Medicare summary files and the preceding hospital stay. Principal Findings: Preferred SNFs exhibited better performance across publicly reported quality measures. Patients admitted to preferred SNFs exhibited shorter stays, lower Medicare payments, and lower probability of SNF readmission relative to nonpreferred SNFs. Conclusions: Our results imply that health systems selected SNFs with lower resource use and better performance on quality measures. Thus, the trend toward preferred provider networks could have implications for Medicare spending and patient health.